2022
DOI: 10.1101/2022.03.05.483133
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Potent universal-coronavirus therapeutic activity mediated by direct respiratory administration of a Spike S2 domain-specific human neutralizing monoclonal antibody

Abstract: Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2) marks the third novel β-coronavirus to cause significant human mortality in the last two decades. Although vaccines are available, too few have been administered worldwide to keep the virus in check and to prevent mutations leading to immune escape. To determine if antibodies could be identified with universal coronavirus activity, plasma from convalescent subjects was screened for IgG against a stabilized pre-fusion SARS-CoV-2 spike S2 domain, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 47 publications
1
13
0
Order By: Relevance
“… 142 Candidate pan-sarbecovirus mAbs targeting the spike protein have been variously referred to as cluster VII, class IV, or receptor binding domain (RBD) core cluster II ( table 3 , figure ): examples of these mAbs include S2X259 40 and DH1047. 143 Other pan-sarbecovirus mAbs belong to the class I cluster I receptor-binding motif (RBM; eg, S2K146 31 ) or class 3 (eg, sotrovimab), or bind to the base of the stem-helix at the HR2 boundary in the S2 subunit (eg, CV3-25, 144 1249A8, 44 and the CC series 145 ). Each of the S2 broadly neutralising antibodies have lower half-maximal inhibitory concentrations than anti-RBD antibodies, which could make the translation into clinically useful doses difficult; however, experiments in animal models suggest protection at low doses, 42 , 43 probably due to additional effector functions.…”
Section: Perspectivesmentioning
confidence: 99%
“… 142 Candidate pan-sarbecovirus mAbs targeting the spike protein have been variously referred to as cluster VII, class IV, or receptor binding domain (RBD) core cluster II ( table 3 , figure ): examples of these mAbs include S2X259 40 and DH1047. 143 Other pan-sarbecovirus mAbs belong to the class I cluster I receptor-binding motif (RBM; eg, S2K146 31 ) or class 3 (eg, sotrovimab), or bind to the base of the stem-helix at the HR2 boundary in the S2 subunit (eg, CV3-25, 144 1249A8, 44 and the CC series 145 ). Each of the S2 broadly neutralising antibodies have lower half-maximal inhibitory concentrations than anti-RBD antibodies, which could make the translation into clinically useful doses difficult; however, experiments in animal models suggest protection at low doses, 42 , 43 probably due to additional effector functions.…”
Section: Perspectivesmentioning
confidence: 99%
“…Moreover, two studies have shown that CC40.8 and S2P6 protect mice and hamsters from SARS‐CoV‐2 challenge 152,153 . Two recent studies reported that stem helix antibodies could also be isolated from vaccinated COVID‐19 patients and exhibit protection against SARS‐CoV‐2 and MERS‐CoV in animal models, further suggesting universal vaccine design to this stem helix epitope site is promising for eliciting pan‐betacoronavirus protection if potency can be increased 154,244 . Since the S2 stem helix is highly conserved across betacoronaviruses whether there is a germline convergent response with conserved motifs to betacoronaviruses, warrants further investigation.…”
Section: Neutralizing Epitopes On Sars‐cov‐2 Spikementioning
confidence: 99%
“…Therefore, we next investigated whether this mechanism of viral spread is resistant to SARS-CoV-2 specific neutralizing antibodies (Abs). The main analyses were performed using receptor-binding domain (RBD)-specific neutralizing human monoclonal antibody (hMAb) 1213H7 ( 27 , 28 ) and two human immune sera. Samples were tested with replication-competent CoV-2/α in a standard plaque reduction neutralization test (PRNT; see Materials and Methods for details).…”
Section: Resultsmentioning
confidence: 99%
“…The PRNT was performed as previously described ( 51 ). Briefly, serum samples from the unspecified, immunized individuals were incubated at 56°C for 1 h. hMAb 1213H7 ( 27 , 28 ) and other virus-neutralizing hMAbs were kindly provided by J. Kobie (University of Alabama at Birmingham). hMAbs and sera were serially (2-fold) diluted in PBS supplemented with 1% FBS and 250 PFU/mL of CoV-2/α.…”
Section: Methodsmentioning
confidence: 99%